An Efficient End-to-End User Interface Testing Method for Web Applications - Le Khanh, Trinh; Pham-Hoang, An; Hoang-Van, Quyen; Bui-The, Cong; Cao-Thi-Minh, Tam; Hung, Pham Ngoc (VNU Journal of Science: Computer Science and Communication Engineering; Vol 41 No 1 (2025), 2025)
This paper proposes a novel end-to-end UI testing method by introducing a domain-specific language named User Behavior Language (UBL) for specifying UI test scenarios. The UBL provides a concise and intuitive syntax for describing UI interactions, enabling rapid test script creation and reducing the learning curve for non-technical testers. Additionally, UBL allows for the specification of constraints between interactions, facilitating the modeling of complex user workflows and enforcing application-specific rules. We also propose a test case generator that utilizes the UBL and the test data to automatically generate a comprehensive suite of test cases, covering both expected and abnormal user behavior. The effectiveness of the proposed UI testing method was validated through a comparative analysis with Katalon Studio by testing some functionalities of SauceDemo, a benchmark Website for UI testing.